FITOREMEDIASI PHOSPAT DENGAN PEMANFAATAN ENCENG GONDOK (EICHHORNIA CRASSIPES) (STUDI KASUS PADA LIMBAH CAIR INDUSTRI KECIL LAUNDRY) - Hardyanti, Nurandani; Rahayu, Suparni Setyowati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Small laundry was one of home industries that grown rapidly. Small laundry industries usually disposed their  wastewater  straightly  to  the  city  drain  system  without  any  treatment  before.  It caused a large amount of phosphate accumulating in the sewage. Because of the environment was  unable  to handle  it  by  themselves,  we  needed  a  simple,  cheap,  and  applicative  way  to reduce phosphate. Phytoremediation was one of methods to remove phosphate. This research used  water  hyacinth. Phytoremediation  was  be  done  by  planting  water  hyacinth  in  the phosphate  wastewater.  By  doing this  we  expected  that  water  hyacinth  would  absorb  the phosphate  from  the  water.  The experiments  was  taken  for  5  days  with  phosphate concentrations of 200 mg/liters; 250 mg/liters; 300mg/liters. At early concentrations of 200mg/l showed that water hyacinth could reduce phosphate until 24.03% or about 144,1603 mg, for the early  concentrations  of  250  mg/l  showed  that  water  hyacinth could  reduce  22.95%  or  about 172.1209 mg and for the early concentrations of 300 mg/liters showed that water hyacinth could absorb about 20,87 % or around 187.860 mg. From the statistic test showed that life time in the wastewater gave a significant result to the ability in absorbing phosphate by the water hyacinth.